2007
DOI: 10.1177/1049731506295860
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Intermediate Outcomes of a Faith-Based Residential Prisoner Reentry Program

Abstract: Objective: This study examined intermediate outcomes of a faith-based prisoner reentry program by assessing how client spirituality related to client- and program-level characteristics, investigating differences between completers and terminators, and examining how religious preference, religiosity/spirituality, religious salience, and incarceration's impact on spirituality influenced program completion, satisfaction, and perceived progress. Method: The study employed independent t tests, chi-square tests, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
19
0
1
Order By: Relevance
“…Research found that FBOs have a higher than expected presence in five types of services-food, housing/shelter, other human services, civil rights, and recreation (Graddy, 2006). A study conducted by Roman, Wolf, Correa, and Buck (2007) determined that homelessness and level of spiritual change were the sole significant predictors for program completion, satisfaction, and progress. Conversely, this study also concluded that individuals who stayed in the program longer reported lower levels of religiosity and were less likely to report that a spiritual change had occurred.…”
Section: Programmatic Outcomesmentioning
confidence: 99%
“…Research found that FBOs have a higher than expected presence in five types of services-food, housing/shelter, other human services, civil rights, and recreation (Graddy, 2006). A study conducted by Roman, Wolf, Correa, and Buck (2007) determined that homelessness and level of spiritual change were the sole significant predictors for program completion, satisfaction, and progress. Conversely, this study also concluded that individuals who stayed in the program longer reported lower levels of religiosity and were less likely to report that a spiritual change had occurred.…”
Section: Programmatic Outcomesmentioning
confidence: 99%
“…Al mismo tiempo, la evaluación de la eficacia de los programas basados en la fe también puede verse afectada por la forma en que las evaluadoras entienden y tratan dichas iniciativas. De hecho, podría suceder que los programas basados en la fe sean tratados por evaluadores como cualquier otro programa, con poco enfoque en cómo las creencias espirituales/religiosas a nivel de cliente u otros aspectos de la fe de la persona pueden influir en los resultados (Roman et al, 2007).…”
Section: ¿Cuál Es La Eficacia De Los Programas Basados En La Fe?unclassified
“…The faith community is considered uniquely positioned to influence the thinking of young people especially (Drake, Aos, & Miller, ; Ericson, ; Johnson & Jang, 2012), through faith‐based activities, mentoring, and social support. The building of social support, trust, and hope for the future have all been documented by participants in faith‐based community re‐entry programmes (Roman, Wolff, Correa, & Buck, ; Armstrong, ; Roberts & Stacer, ). Social control and identity transformation theories are commonly invoked to explain the prosocial effect of religiosity; positing individuals are less likely to engage in delinquency if they have stronger prosocial attachments, a stake in conformity, and spend much of their time engaged in structured conventional activities (Johnson, Larson, Jang, & Li, ; Giordano, Longmore, Schroeder, & Seffin, ).…”
Section: Introductionmentioning
confidence: 99%